Remote Sensing of Water Quality in the Valle de Bravo Reservoir, Mexico - World Bank (World Bank, Washington, DC, 2021)
This case study assessed ongoing initiatives to address surface water pollution issues in Mexico, working in partnership with the Comision Nacional del Agua (CONAGUA), the national agency responsible for the administration of water resources and its management. Particular focus was placed on a pilot case study application of remote sensing techniques to detection of water-quality issues in the Valle de Bravo reservoir. This assessment will contribute to a better understanding of options for water-quality remote sensing capabilities and needs. It will assist in identifying appropriate remote sensing tools and devising an application strategy to support decision making regarding the targeting and monitoring of nutrient pollution prevention and mitigation measures.